The London memory service audit and quality improvement programme. (October 2019) - Cook, Laura D.; Nichol, Katie E.; Isaacs, Jeremy D.
Abstract : Aims and method: Memory services have expanded significantly in the UK, but limited performance data have been published. The aim of this programme was to determine variation in London memory services and address this through service improvement projects. In 2016 London memory services were invited to participate in an audit consisting of case note reviews of at least 50 consecutively seen patients. Results: Ten services participated in the audit, totalling 590 patients. Variation was noted in neuroimaging practice, neuropsychology referrals, diagnosis subtype, non-dementia diagnoses, waiting times and post-diagnostic support. Findings from the audit were used to initiate four service improvement projects. Clinical Implications: Memory services should consider streamlining pathways to reduce waiting times, implementing pathways for patients who do not have dementia, monitoring appropriateness of neuroimaging, and working with commissioners and primary care to ensure that access to post-diagnostic interventions is consistent with the updated National Institute for Health and Care Excellence (NICE) dementia guideline. Declaration of interest: J.D.I. received an honorarium from Biogen for an advisory board. He has been Principal Investigator in clinical trials sponsored by Roche, Merck and Lupin pharmaceuticals. He was a member of the 2018 NICE dementia clinical guideline committee.